The Role of Corporate Governance in Shaping IFR Practices of Listed Companies in Sri Lanka - Raveeswaran, Kiruththika; Vickneswaran, Anojan (Universitas Syiah Kuala, 2024)
Objective This study investigates the relationship between corporate governance characteristics and Internet Financial Reporting (IFR) in the context of listed companies in the Colombo Stock Exchange (CSE).Design/Methodology The key metrics for assessing corporate governance characteristics include board size, independence, CEO duality, women in the board, audit committee independence, and ownership concentration. These data were derived from the published annual reports. Employing content analysis, the study measures IFR disclosure using secondary data from the published annual reports of 201 listed companies in Sri Lanka.Results The mean value of listed companies' IFR disclosure is 50.66% in Sri Lanka. Regression results show that audit committee independence and ownership concentration significantly impact the IFR. However, no statistical evidence supports other variables' significant impact on IFR.Research limitations/implications This study relies upon only 201 listed firms data for a financial year in Sri Lanka and the statistical model includes only five corporate governance-related variables. The study's findings contribute to the reform of corporate governance practices, corporate governance literature, and information asymmetry theory. Moreover, results have practical implications for the composition of the board and audit committee.Novelty/Originality This study contributes to the existing literature and lays the groundwork for future research by providing new insights into the adoption of IFR practices in Sri Lanka and other similar nations. Examining the impact of corporate governance on IFR practices in listed firms within a developing country sheds light on the significance of corporate governance and IFR.